From Evidence to Action: Enhancing Collaborative Practice in Healthcare Teams - ALANAZI, ABDULAZIZ NASSER; ALSAAD, FATIMAH NASSER; ALGETHAMI, KHALID HUSSAIN ZUWAYYID; ALREFAEI, HAMED SALEH SAEED; ALGETHAMI, ABDULKARIM SALEEM ZUWAYYID; ALSNADI, SALEM MOHMMED; ALQAHTANI, FAHAD NASSER ABDULLAH; ALQAHTANI, ABDULLAH HAMAD A; ALHOSSAN, ABDULMAJED SALEH; ALHARTHI, AHMED ABDULALI KHALID; et al. (Journal of Posthumanism, 2024)
Evidence-based practice (EBP) has emerged as a transformative framework in healthcare, bridging the gap between research evidence, clinical expertise, and patient values. Its foundations lie in the recognition that high-quality care cannot rely solely on tradition or intuition but must be informed by systematically gathered evidence. Over the past three decades, EBP has become a standard expectation in healthcare institutions worldwide, guiding decision-making and ensuring safe, effective, and patient-centered outcomes.